Teaching Methods and Gender as Determinants of Academic Achievement of Students in Agriculture Subject in Ndhiwa Sub County, Kenya - Ogweno, Peter Oyier; Ongang’a, Peter Odhiambo; Mbai, Quinter Akeyo (Journal of Education and Practice, 2024)
Purpose: This study attempted to determine if the three teaching techniques utilized in this study, namely the demonstration-teaching method (DTM), the lecture-teaching method (LTM), and problem-based learning (PBL), would have a substantial impact on student's academic performance dependent on their gender. Methodology: The study used a quasi-experimental design. The researchers employed a non-equivalent control group for the pre-test and post-test. PBL and DTM were the treatments, while LTM served as the control. The sample size consisted of 779 pupils, out of 7124 students. Using stratified random sampling, 18 secondary schools and 18 agriculture teachers were selected. Each of the three methods of instruction was assigned to six schools. Agriculture achievement test was used to collect data from students. Descriptive statistics, the T-test, and covariance analysis were used as data analysis techniques. Findings: The outcomes of the study revealed that female students fared better (51.356) than male students (48.852). Educators may better understand the advantages of PBL and DTM as teaching methodologies because the findings are that both are more successful at disseminating knowledge. Unique Contribution to Theory, Policy and Practice: The findings may help higher education institutions to emphasize on the use PBL and DTM when they are delivering their lectures to students of education. This strategy will help students improve students’ performance once they graduate and they are employed to teach agriculture subject.